Historical-pedagogical analysis of model and simulation development as a part of tactical training of military professionals - KOS, Mykola (Journal of Education, Technology and Computer Science, 2013)
We have provided a short description of development of models and simulation of tactical and strategic actions in training of military professional. We believe that better and more rigorous research of development and new trends of models and simulation is needed in order to gain the necessary knowledge on how to use their experience in development of perspective systems of models and simulation of combat actions for Ukrainian Armed Forces. This is especially true for the training of future officers in Military Higher Education Institutions. A further line of research may be the analysis of development of national models and simulation of various actions in military sphere, particularly in system of military education.